Fusing N-heteroacene analogues into one “kinked” molecule with slipped two-dimensional ladder-like packing - Zhang, Jing (2018)
An unexpected “kinked” N-heteroacene with a slipped two-dimensional ladder-like packing feature is produced from the conventional condensation reaction. The as-obtained compound [2,2′]bi(5,12-bis(TIPS)piperazin-3-one[2,3-b]phenazine) (2BPP) consists of two identical backbones (5,12-bis(TIPS)piperazin-3-one[2,3-b]phenazine), which are fused together through a C[double bond, length as m-dash]C double bond and two intramolecular H-bonds. A study on the charge carrier transport indicates that a 2BPP single crystal has a hole mobility up to 0.3 cm2 V−1 s−1, while theoretical calculations suggest that this compound might possess potential well-balanced ambipolar charge-transport characteristics.